1990
DOI: 10.1084/jem.171.5.1635
|View full text |Cite
|
Sign up to set email alerts
|

Antibody activity in ankylosing spondylitis sera to two sites on HLA B27.1 at the MHC groove region (within sequence 65-85), and to a Klebsiella pneumoniae nitrogenase reductase peptide (within sequence 181-199).

Abstract: 74 overlapping peptides of varying lengths from Klebsiella pneumoniae nitrogenase reductase (residues 181-199) and from the HLA B27.1 molecule (residues 65-85) were synthesized and tested by ELISA against sera from HLA B27+ ankylosing spondylitis (AS) patients, and sera from HLA B27+ and HLA B27- healthy first-degree relatives. Antibody activity in AS sera to Klebsiella peptides of four to eight amino acids was maximal with the peptide NSRQTDR. Activity to HLA B27 peptides was maximal with the peptide KAKAQTDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 20 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…Further support of this hypothesis is the finding that HLA class II antigen associated with rheumatoid arthritis shared the same amino acid sequences with some viral antigens ( Albani & Carson, 1996 ). Data from serologic studies also indicated that patients with AS had high incidence of antibodies against microbial pathogens (Ewing et al, 1990). This study indicate that AS patient sera contain antibodies which were reactive to K. pneumoniae nitrogenase peptides and HLA B27.1 peptides, and that there are at least two epitopes in the alpha 1 domain at the groove region, that are autoantigenic.…”
Section: Theory Of Molecular Mimicry and Arthritogenic Peptidessupporting
confidence: 59%
“…Further support of this hypothesis is the finding that HLA class II antigen associated with rheumatoid arthritis shared the same amino acid sequences with some viral antigens ( Albani & Carson, 1996 ). Data from serologic studies also indicated that patients with AS had high incidence of antibodies against microbial pathogens (Ewing et al, 1990). This study indicate that AS patient sera contain antibodies which were reactive to K. pneumoniae nitrogenase peptides and HLA B27.1 peptides, and that there are at least two epitopes in the alpha 1 domain at the groove region, that are autoantigenic.…”
Section: Theory Of Molecular Mimicry and Arthritogenic Peptidessupporting
confidence: 59%
“…The question is whether any of these undoubted examples of molecular mimicry actually give rise to anti-B27 immune responses and whether these are in any way pathological. Low titres of antibody to cross-reacting epitopes have been described in patients with ankylosing spondylitis and reactive arthritis (Schwimmbeck et al, 1987;Ewing et at., 1990) but their significance is unclear (Tsuchiya, Husby & Williams, 1989) and it is difficult to envisage these diseases as being antibody mediated. Since the examples of molecular mimicry have been identified using antibodies, they do not provide much information about the possibility of molecular mimicry occurring at the T cell level; T cells specific for a microbial antigen would have to crossrecognize B27 occupied by a self-peptide.…”
Section: J S H Gaston Department Of Rheumatology University Of Bimentioning
confidence: 99%
“…Ewing et al 77 used a variety of synthetic peptides derived from HLA-B27 as substrates in ELISA systems. Analysing the specificity of a number of patient sera recognising peptides from B*2705, they found two different reactive sites in the B27 peptides.…”
Section: Resultsmentioning
confidence: 99%
“…A very elegant study was carried out by Ewing et al 77. Using overlapping peptides of eight residues from the B*2705 molecule, they showed that in fact the antibody response against the part of B*2705 containing the Klebsiella homologous sequence was not directed to the complete homologous 72-QTDRED-77 sequence, but rather to flanking regions that included only a few of the homologous residues—that is, 68-KAKAQTDR-75 and 76-REDLRTLL-83 of HLA-B27.…”
Section: Resultsmentioning
confidence: 99%